Search for rapid radio variability in a sample of gamma-ray emitting blazars with the radio telescopes of IAR - Galante, Camila Ailen (2022)
Blazars - active galactic nuclei in which one of the jets is pointing toward the observer - show flux density variations throughout the entire electromagnetic spectrum on time scales ranging from minutes to years. The occurrence of gamma-ray emission in these objects indicates the presence of populations of relativistic particles. Such particles should also emit in radio frequencies by synchrotron mechanism. The investigation of microvariability at radio-wavelengths can provide information about the non-thermal processes that occur inside the relativistic jets. We present results of 1.4-GHz variability observations of a sample of blazars, selected because of their strong gamma-ray emission. The observational campaign was carried out in February, 2021, using the upgraded Esteban Bajaja radio telescope of the Instituto Argentino de Radioastronomía.